PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT TERHADAP HASIL BELAJAR TAJWID - Wardani, Dian Kusuma; Mukarromah, Niswatin (UIN Antasari Banjarmasin, 2022)
ABSTRACTThe learning model determines the results achieved by student learning. The use of inappropriate models will make students passive in the learning process. Team Games Tournament (TGT) is a collaborative model that triggers student collaboration and creativity. This study aims to test the effectiveness of the TGT model in learning recitation of the second grade students of Wustho Madin At-Takmiliyah An-Najiyah 1 Jombang. This study uses the entire population. The method used is quasi-experimental. The data analysis method for this study used the Wilcoxon paired pair test. The results of this study indicate that the use of the TGT learning model has a significant effect on the learning outcomes of class II Wustho students.KEYWORDS: Team-Games Tournament; Tajweed; Learning Achievement. ABSTRAKModel pembelajaran menentukan hasil yang dicapaian pembelajaran siswa. Penggunaan model yang kurang tepat akan membuat siswa pasif dalam proses pembelajaran. Team Games Tournament (TGT) merupakan model kolaboratif yang memicu kolaborasi dan kreativitas siswa. Penelitian ini bertujuan untuk menguji efektivitas model TGT pada pembelajaran tajwid pada siswa kelas II Wustho Madin At-Takmiliyah An-Najiyah 1 Jombang. Penelitian ini menggunakan seluruh populasi. Metode yang digunakan adalah quasi-eksperimen. Metode analisis data untuk penelitian ini menggunakan uji pasangan berpasangan Wilcoxon. Hasil penelitian ini menunjukkan bahwa penggunaan model pembelajaran TGT berpengaruh signifikan terhadap hasil belajar siswa kelas II Wustho.KATA KUNCI: Team-Games Tournament; Tajwid; Hasil Belajar.